ADAPTATION OF RUSSIAN FIRMS TO THE EXTERNAL ENVIRONMENT CHANGES: THE ROLE OF ELECTRONIC BUSINESS - A. Trachuk; N. Linder (Управленческие науки, 2016)
The article2 discusses the possibility of using e-business tools for companies to save strategic stability under a shrinking market. The analytical study results in singling out consumer preferences under unstable external environment, as well as Russian companies’ opportunities of using e-business to form a new value. Advantages of e-business to maintain and increase market share under the conditions of consumer drop in demand are defined. The consumer survey and its results analysis have been conducted using the method of content analysis. This approach allowed to draw some conclusions regarding the features of building business models using e-business, to identify opportunities for transformation, aimed not only at improving the efficiency and competitiveness, but also on creating a new value for consumers in order to maintain and increase existing market share and to establish new markets of consumers.business allows to create a new value based on increasing efficiency by reducing, first of all, transaction costs, by decreasing asymmetric information, increasing the speed of transactions and so on. E-business strategies make it easier to create the effect of customer “locking”, i. e. the creation of various loyalty programs, the deepening of customization through the use of Big Data tools, consisting in the initial data analysis. The results of the latter determine the problems and opportunities to improve offers for customers.